Peran Wing In Ground Effect Craft (WIG) Terhadap Peningkatan Pendapatan Asli Daerah Jepara-Karimunjawa - Susilo Hadi Wibowo; Mashudi Rofiq; Dimas Pratama Yuda; Prapti Utami (Politeknik Ilmu Pelayaran Semarang, 2021)
Tourism objects in Jepara Regency and Karimunjawa District can be relied on for both natural tourism and marine biodata so that they attract tourists both domestically and internationally. From 2009 to 2019 there was an increase even though the amount was not constant, this was enough to increase the local Regional Revenue Budget. one way that can raise prestige in the world of tourism in the era of globalization and the digital era 4.0 is by adding means of sea ship transportation with the model of a winged passenger ship, which can fly low above sea level, faster and more efficiently by displaying the Weigh-In Ground Effect (WIG). The purpose of this study is to describe the increase in local revenue (PAD) for tourism objects with the addition of a fleet of fast passenger boats based on wing in grounds effect craft (WIG) at tourism objects in Karimunjawa, Jepara. This research uses quantitative data with associative type. The data collection technique used by the researcher is based on documentation, library studies, and the results of the development of previous researchers. From the results of the study, it can be concluded that there is a significant effect of increasing tourism supporting elements, the number of infrastructure facilities, and tourism promotion costs on increasing regional income.